(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Propofol gains popularity due to its smooth induction and rapid recovery. But one of its side effects is pain during injection. So, the aim of this study was to compare the efficacy of tramadol and lidocaine pretreatment for alleviation of pain on propofol injection in our setting. Materials and methods: 80 patients of either sex (ASA grade I and II, age 20-50 years) who underwent elective Surgery under general anaesthesia were randomized into two equal groups (n=40). Group L (Control group) received pretreatment injection 2% lidocaine 40mg (2ml) Group T received pretreatment injection tramadol 50 mg (2ml). After that, 1/4th of calculated induction dose of propofol (2mg/kg) was administered. The level of pain was evaluated by four point verbal response scale. Results: The overall incidence of pain on propofol injection was lower in lidocaine (20%) than in tramadol group (22.5%). The incidence of score ‘0’ (No pain) was higher in lidocaine (80%) than in tramadol group (77.5%) but it is not statistically significant (p >0.05). Conclusion: pretreatment with 2% lignocaine and tramadol effectively reduced the incidence and severity of propofol injection pain. JCMCTA 2021 ; 32 (2) : 90-94